Persepsi Kesesuaian Diklat PKP Dengan Peningkatan Kompetensi dan Kinerja Peserta - Siswanto, Eddy (Jurnal Ilmiah Global Education, 2025)
The Supervisory Leadership Training (Pelatihan Kepemimpinan Pengawas or PKP) is a managerial competence development program for Indonesia’s civil servants (ASN), aimed at enhancing leadership quality and organizational performance in the public sector. This cross sectional study was conducted descriptively to assesses the perceptions of 2023 PKP alumni regarding the usefulness of the training and its impact on their competencies and the application of leadership values in the workplace. The study employs a conceptual framework combining Systems Theory (Input-Process-Output) and the Health Belief Model (HBM). Data were collected from 21 respondents (70% of the population) via an online questionnaire and analyzed using descriptive quantitative methods. Results indicate that 86% of respondents had a positive perception of the training, particularly in reinforcing ethics and integrity, creative thinking, and public service communication. However, 76.19% felt that the training did not fully address their specific work-related competency needs, citing the need for additional technical skills, benchmarking opportunities, and more supportive institutional systems. Topics such as Organizational Diagnosis, Budget Planning (RKA), and Supervisory Management were reported as difficult to implement due to misalignment with field conditions and limited organizational support. One respondent (3.3%) explicitly stated that the training outcomes were incompatible with their unit’s work system. These findings underscore the need to strengthen training design based on real needs (Training Needs Analysis), enhance learning methods through mentoring and hands-on practice, and provide post-training support to ensure effective transfer of learning. The evaluation offers concrete recommendations to improve training policy, including the development of adaptive materials, implementation of hybrid learning models, and increased participation in data-driven evaluations